2023
DOI: 10.1108/ijlm-10-2022-0410
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability dichotomies of used clothes supply chains: a critical review of key concerns and strategic resources

Abstract: PurposeUsed clothes supply chains are becoming increasingly complex, fragmented and less transparent due to rising volumes of discarded clothes and its dispersed reverse logistics operations across the Global North (GN) and Global South (GS). While it has a promising impact on circular economy and international trade growth, increasing exports of used clothes and overflowing landfills raise some negative concerns on its overall sustainability. This paper addresses the dichotomy that exists in terms of interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…The nine antecedents of environmental VU mostly pointed to the high environmental footprints of the cross-border transport of used clothes, either due to a lack of scale and infrastructure, cost-efficient handling therein or adequate knowledge about processing activities. While increasing competition for NPOs largely hampers their ability to generate higher social value, such as creating competitive jobs outside the labour market, the lack of adequate traceability along the CSC has negative social spillovers in the Global South, where extremely low-quality used clothes often end up in landfills (Dissanayake and Pal, 2023). Despite fewer antecedents, it cannot be concluded that social value is already adequately captured in used clothing CSCs; however, social sustainability has yet to receive comprehensive attention and understanding in the CSC context, as also indicated by Walker et al .…”
Section: Discussionmentioning
confidence: 99%
“…The nine antecedents of environmental VU mostly pointed to the high environmental footprints of the cross-border transport of used clothes, either due to a lack of scale and infrastructure, cost-efficient handling therein or adequate knowledge about processing activities. While increasing competition for NPOs largely hampers their ability to generate higher social value, such as creating competitive jobs outside the labour market, the lack of adequate traceability along the CSC has negative social spillovers in the Global South, where extremely low-quality used clothes often end up in landfills (Dissanayake and Pal, 2023). Despite fewer antecedents, it cannot be concluded that social value is already adequately captured in used clothing CSCs; however, social sustainability has yet to receive comprehensive attention and understanding in the CSC context, as also indicated by Walker et al .…”
Section: Discussionmentioning
confidence: 99%
“…The PRISMA 2020 statement (from here on PRISMA) consists of a detailed 27-item checklist that is worked through over four phases, and thus can be replicated by others wishing to conduct the same research . Moreover, PRISMA is a commonly used tool and has been previously utilized in SLRs that also focus on a highly complex and topical areas (e.g., Dissanayake and Pal; Jagaba et al). , The PRISMA 2020 checklist is commonly accompanied by a flowchart diagram, visualized in Figure , which outlines the individual steps taken to reach the final number of articles analyzed. These are further detailed in the following sections.…”
Section: Methodology and Materials Collectionmentioning
confidence: 99%
“… 33 Moreover, PRISMA is a commonly used tool and has been previously utilized in SLRs that also focus on a highly complex and topical areas (e.g., Dissanayake and Pal; Jagaba et al). 34 , 35 The PRISMA 2020 checklist is commonly accompanied by a flowchart diagram, visualized in Figure 2 , which outlines the individual steps taken to reach the final number of articles analyzed. These are further detailed in the following sections.…”
Section: Methodology and Materials Collectionmentioning
confidence: 99%